Exposure to bacterial and fungal bioaerosols in facilities processing biodegradable waste - Kontro, Merja H.; Kirsi, Maija; Laitinen, Sirpa K. (Frontiers in Public Health, 2022)
The aim of the study was to determine the exposure of workers within biodegradable waste processing facilities to bacteria and fungi to identify any exposures of potential concern to health. Occupational measurements were performed in six composting and three bioenergy (bioethanol or methane/biogas) producing facilities. Bioaerosols were measured from breathing zones with Button aerosol or open face cassette filter samplers, and swab specimens were taken from the nasal mucous membranes of the workers. Aspergillus fumigatus, Bacillus cereus group, Campylobacter spp., Salmonella spp., Streptomyces spp., and Yersinia spp. were determined by real-time polymerase chain reaction (qPCR). A. fumigatus, and mesophilic and thermophilic actinobacteria were also cultivated from filters. Bacterial airborne endotoxins collected by IOM samplers were analyzed using a Limulus assay. Bioaerosol levels were high, especially in composting compared to bioenergy producing facilities. Endotoxin concentrations in composting often exceeded the occupational exposure value of 90 EU/m3, which may be harmful to the health. In addition to endotoxins, the concentrations of A. fumigatus (up to 2.4 × 105 copies/m3) and actinobacteria/Streptomyces spp. (up to 1.6 × 106 copies/m3) in the air of composting facilities were often high. Microbial and endotoxin concentrations were typically highest in waste reception and pre-treatment, equal or decreased during processing and handling of treated waste, and lowest in wheel loader cabins and control rooms/outdoors. Still, the parameters measured in wheel loader cabins were often higher than in the control sites, which suggests that the use of preventive measures could be improved. B. cereus group, Salmonella spp., and Yersinia spp. were rarely detected in bioaerosols or nasal swabs. Although Campylobacter spp. DNA was rarely detected in air, as a new finding, Campylobacter ureolyticus DNA was frequently detected in the nasal mucous membranes of workers, based on partial 16S rDNA sequencing. Moreover, especially A. fumigatus and C. ureolyticus spp. DNA concentrations in swabs after the work shift were significantly higher than before the shift, which indicates their inhalation or growth during the work shift. Microbial qPCR analysis of bioaerosols and swab samples of nasal mucosa allowed measuring exposure in various work operations and during the work shift, identifying problems for health risk assessment to improve working conditions, and evaluating the effectiveness of preventive measures and personal protection of workers.